2017
DOI: 10.1111/tpj.13504
|View full text |Cite|
|
Sign up to set email alerts
|

SHOOT MERISTEMLESS trafficking controls axillary meristem formation, meristem size and organ boundaries in Arabidopsis

Abstract: The shoot stem cell niche, contained within the shoot apical meristem (SAM) is maintained in Arabidopsis by the homeodomain protein SHOOT MERISTEMLESS (STM). STM is a mobile protein that traffics cell-to-cell, presumably through plasmodesmata. In maize, the STM homolog KNOTTED1 shows clear differences between mRNA and protein localization domains in the SAM. However, the STM mRNA and protein localization domains are not obviously different in Arabidopsis, and the functional relevance of STM mobility is unknown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 57 publications
3
36
0
Order By: Relevance
“…To test whether strong subcellular localization interferes with the mobility of the protein, we generated TMO7-GFP protein with SV40 nucleus localization (NLS) or nuclear export signals (NES) at the N- or C-terminus of TMO7-GFP, respectively (NLS-TMO7-GFP; TMO7-GFP-NES). Like in other mobile proteins (Balkunde et al, 2017; Gallagher et al, 2004; Rodriguez et al, 2016), the nuclear localization signal restricted TMO7 movement. Surprisingly however, the NES also hindered its mobility (Fig 5B-D), suggesting that entering as well as leaving the nucleus might be crucial for TMO7 transport.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…To test whether strong subcellular localization interferes with the mobility of the protein, we generated TMO7-GFP protein with SV40 nucleus localization (NLS) or nuclear export signals (NES) at the N- or C-terminus of TMO7-GFP, respectively (NLS-TMO7-GFP; TMO7-GFP-NES). Like in other mobile proteins (Balkunde et al, 2017; Gallagher et al, 2004; Rodriguez et al, 2016), the nuclear localization signal restricted TMO7 movement. Surprisingly however, the NES also hindered its mobility (Fig 5B-D), suggesting that entering as well as leaving the nucleus might be crucial for TMO7 transport.…”
Section: Resultsmentioning
confidence: 90%
“…Intercellular communication is vital for development of multi-cellular organisms (Long et al, 2015), for example to coordinate distant events or locally organize tissues (Balkunde et al, 2017; Corbesier et al, 2007; Kurata et al, 2005; Nakajima et al, 2001; Pi et al, 2015; Sessions et al, 2000; Tamaki et al, 2007; Yadav et al, 2011). Plant cell walls provide robust physical support to build elaborate tissues and structures; however, cell walls also hamper cell migration, and it is therefore important for plant cells to receive positional cues from their surroundings for proper development (ten Hove et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…To test whether strong subcellular localization interferes with the mobility of the protein, we generated TMO7-GFP protein with SV40 nucleus localization (NLS) or nuclear export signals (NES) at the N or C terminus of TMO7-GFP, respectively (NLS-TMO7-GFP; TMO7-GFP-NES). Like in other mobile proteins (Balkunde et al, 2017;Gallagher et al, 2004;Rodriguez et al, 2016), the nuclear localization signal restricted TMO7 movement. Surprisingly, however, the NES also hindered its mobility (Fig.…”
Section: Protein Sequence Elements and Subcellular Localization Definmentioning
confidence: 93%
“…It has been known for some time that intercellular communication is vital for the development of multicellular organisms (Barlow and Carr, 1984;Bonner, 1998;Long et al, 2015;Niklas and Newman, 2013), for example to coordinate distant events or locally organize tissues (Balkunde et al, 2017;Corbesier et al, 2007;Kurata et al, 2005;Nakajima et al, 2001;Pi et al, 2015;Sessions et al, 2000;Tamaki et al, 2007;Yadav et al, 2011). Plant cell walls provide robust physical support to build elaborate tissues and structures; however, cell walls also prevent cell migration, and it is, therefore, important for plant cells to receive positional cues from their surroundings for proper development (Barlow and Carr, 1984;ten Hove et al, 2015;van den Berg et al, 1995van den Berg et al, , 1997.…”
Section: Introductionmentioning
confidence: 99%
“…CUP-SHAPED COTYLEDON (CUC), encoding a NAC (No Apical Meristem)-domain protein, is involved in the regulation of shoot apical meristem (SAM) formation during organ differentiation [8]. Previous research showed that CUC and SHOOT MERISTEMLESS (STM) regulate each other's expression throughout development, but STM controlled CUC expression in organ boundary region [9]. As a negative regulator of meristem cell accumulation, ULTRAPETALA1 (ULT1) negatively regulates WUS expression during meristem development [10].…”
Section: Introductionmentioning
confidence: 99%